2005
DOI: 10.1126/science.1115455
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Brain: Implications for Explaining Autism

Abstract: Empathizing is the capacity to predict and to respond to the behavior of agents (usually people) by inferring their mental states and responding to these with an appropriate emotion. Systemizing is the capacity to predict and to respond to the behavior of nonagentive deterministic systems by analyzing input-operation-output relations and inferring the rules that govern such systems. At a population level, females are stronger empathizers and males are stronger systemizers. The “extreme male brain” theory posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

50
706
6
25

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 950 publications
(787 citation statements)
references
References 76 publications
(59 reference statements)
50
706
6
25
Order By: Relevance
“…Since autism is a developmental disorder, these genes may affect or regulate the development of sexual dimorphism in the brain and in behavior. 56 The rationale for examining regression was based on previous work by Molloy et al, 27 where 34 families were identified with at least two affected individuals who showed regression. Signals in this earlier study were observed for chromosome 7 at 170.14 cM and chromosome 21 at 16.16 cM.…”
Section: Discussionmentioning
confidence: 99%
“…Since autism is a developmental disorder, these genes may affect or regulate the development of sexual dimorphism in the brain and in behavior. 56 The rationale for examining regression was based on previous work by Molloy et al, 27 where 34 families were identified with at least two affected individuals who showed regression. Signals in this earlier study were observed for chromosome 7 at 170.14 cM and chromosome 21 at 16.16 cM.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have postulated that the cognitive style of a person or the adopted cognitive strategy in a situation is influenced by gender. In the empathizing-systemizing (E-S) theory of sex differences in cognitive style, males are held to be characterized by a stronger systemizing or analytical style, whereas female boast a stronger empathizing style (Baron-Cohen, Knickmeyer, & Belmonte, 2005). Strategy differences have even been advocated when interpreting gender differences in creative thinking.…”
Section: Gender and Cognitive Strategymentioning
confidence: 99%
“…Cross-sectionally, autism's multiplicity of symptom profiles and neurobiological mechanisms makes it imperative to correlate imaging with other measures of potential endophenotypes, heightening the demand for large data sets which can be fractionated according to such measures. In addition, autism is much more common in males than in females, and sex differences extend to symptom profiles (McLennan, Lord, & Schopler, 1993) and possibly to mechanisms (Baron-Cohen et al, 2005), making it important to factor out sex as a variable, and magnifying the problem of sample size in the case of the smaller, female subgroup.…”
Section: The Problemmentioning
confidence: 99%
“…Longitudinally, especially given autism's nature as a developmental disorder, measurements can be expected to change over the course of maturation and aging (Aylward, Minshew, Field, Sparks, & Singh, 2002;Carper, Moses, Tigue, & Courchesne, 2002). [The inconsistency of recent findings on the size of the amygdala at various ages is a case in point (Baron-Cohen, Knickmeyer, & Belmonte, 2005).] The consequent need to control and account for age particularly hampers retrospective efforts to combine separately ascertained samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation